The Value of Corporate Bond Listing - Brittany M. Cole; Nell S. Gullett (The Institute of Academic Research and Publication (IARP), 2024)
We study the impact of bond exchange listing in U.S. publicly traded corporate bond markets. We find that listed corporate bonds have lower estimated bid-ask spreads than unlisted corporate bonds. Specifically, we show that listed bonds have estimated spreads of 0.14 lower than unlisted bond spreads. We find that execution venue matters for listed bonds, and that listed bond executions on the NYSE have higher trading costs than listed bond executions off-NYSE. We show that listed bonds are more volatile than unlisted bonds. Last, we study bond trading around earnings announcements and find a slight increase (decrease) in overall (institutional) volume on earnings announcement days compared to non-announcement days.